Elimu Haina Mwisho: Mwalimu Nyerere ' s Vision of Adult Education - Hall, Budd L. (Papers in Education and Development, 2021)
1970 was solemnly declared by the government of Tanzania Adult Education Year, a national call for the mobilization of learning with, by and for all the people of Tanzania. The declaration of Adult Education Year was a product of the thinking of the late Mwalimu Julius Kambarage Nyerere, the independence leader and founding President of Tanzania. Nyerere ' s thoughts on development, African socialism and politics of the African independence are well known. Drawing from literature and my own experience of working with adult education sub-sector in Tanzania during the Nyerere era, this article documents Nyerere ' s visionary ideas about the role of adult and lifelong learning. The literature is chiefly anchored to documents from the formative years of 1970-1976. It is based on historical records as well as recollections by the author who worked at the Tanzanian Institute of Adult Education from 1970-1975. Keywords: adult education, community-based learning, Elimu Haina Mwisho, Nyerere, social change,